BIOSOLVE‐IV‐registry: Safety and performance of the Magmaris scaffold: 12‐month outcomes of the first cohort of 1, 075 patients. Issue 1 (3rd September 2020) - Verheye, Stefan; Wlodarczak, Adrian; Montorsi, Piero; Torzewski, Jan; Bennett, Johan; Haude, Michael; Starmer, Gregory; Buck, Thomas; Wiemer, Marcus; Nuruddin, Amin A. B.; Yan, Bryan P.‐Y.; Lee, Michael K.‐Y.
Abstract: Objectives: We aimed to assess the safety and performance of the Magmaris sirolimus‐eluting bioresorbable magnesium scaffold in a large patient population. Background: Magmaris has shown good outcomes in small‐sized controlled trials, but further data are needed to confirm its usability, safety, and performance. Methods: BIOSOLVE‐IV is an international, single arm, multicenter registry including patients with a maximum of two single de novo lesions. Follow‐up is scheduled up to 5 years; the primary outcome is target lesion failure (TLF) at 12 months. Results: A total of 1, 075 patients with 1, 121 lesions were enrolled. Mean patient age was 61.3 ± 10.5 years and 19.2% ( n = 206) presented with non‐ST‐elevation myocardial infarction (NSTEMI). Lesions were 3.2 ± 0.3 mm in diameter and 14.9 ± 4.2 mm long; 5.1% ( n = 57) were bifurcation lesions. Device success was 97.3% ( n = 1, 129) and procedure success 98.9% ( n = 1, 063). The Kaplan–Meier estimate of TLF at 12 months was 4.3% [95% confidence interval, CI: 3.2, 5.7] consisting of 3.9% target lesion revascularizations, 0.2% cardiac death, and 1.1% target‐vessel myocardial infarction. Definite/probable scaffold thrombosis occurred in five patients (0.5% [95% CI: 0.2, 1.1]), thereof four after early discontinuation of antiplatelet/anticoagulation therapy. Conclusion: BIOSOLVE‐IV confirms the safety and performance of the Magmaris scaffold in a large population with excellent device and procedure success and a very good safety profile up to 12 months in a low‐risk population.